Assessment of change order impact factors on construction project performance using analytic hierarchy process (AHP) - Gunduz, Murat; Mohammad, Khaled Omar (Technological and Economic Development of Economy, 2020)
Complexity is very high in construction project and constrained by money and time. Change orders are commonly required during the execution of construction projects. They may increase, omit or adjust tasks in the project. Change orders affect the performance of construction job because they disturb current jobs and affect their schedule. The motive behind this study is to outline a complete assessment on change orders impacts. A review on past studies was performed to capture change order factors that affect project performance. Literature review and interviews with the industry professionals were used to finalize the factors into 16 critical factors. A questionnaire was distributed to industry specialists to capture the effect of these 16 factors on project performance. Complete answers of 102 surveys were received. Analytic Hierarchy Process (AHP) and Relative Important Index (RII) were utilized to analyze the responses. This study differs from other past studies by studying change order impact factors on three different change order types namely additional, omission and substitutional works. The most important change orders impacts factors as per the analysis outcomes are increased project management efforts, increased project re-planning, loss of efficiency due to work interruption, increased reworks/demolition works and delay of payments. This paper would help construction professionals to recognize change order impacts and would assist them in taking proactive actions to limit these impacts.First published online 19 November 2019